Energy industry in Mexico. Policy change and rethinking of energy reform results - I. A. Guliyev; Yu. V. Solovova (Ибероамериканские тетради, 2020)
The article explores the energy industry in Mexico. The authors analyze the shift of energy policy course (after the new president took office in 2019) built upon ensuring energy sovereignty as a central element. The article identifies the main directions of current energy policy as reflected in key strategic documents, including the National Development Plan 2019-2024 and the National Electricity Sector Development Programme 2019-2033. Characteristics of the energy reform in 2013, its background and content, as well as the results are presented, and regulatory framework of energy sector formed during the reform is outlined.